2023
DOI: 10.3390/ijerph20053993
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Reported Strengths and Limitations of Aboriginal and Torres Strait Islander Health Research: A Narrative Review of Intervention Studies

Abstract: High quality intervention research is needed to inform evidence-based practice and policy for Aboriginal and Torres Strait Islander communities. We searched for studies published from 2008–2020 in the PubMed database. A narrative review of intervention literature was conducted, where we identified researcher reported strengths and limitations of their research practice. A total of 240 studies met inclusion criteria which were categorised as evaluations, trials, pilot interventions or implementation studies. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 256 publications
0
4
0
Order By: Relevance
“…Genuine engagement, despite being identified as a key enabler for interventions aiming to improve the health of Aboriginal and Torres Strait Islander peoples, is often curtailed due to restrictions on time and resources ( 46 ). Modifications to EBCD in this study align with best practice approaches for health co-design projects with Aboriginal and Torres Strait Islander people and communities ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genuine engagement, despite being identified as a key enabler for interventions aiming to improve the health of Aboriginal and Torres Strait Islander peoples, is often curtailed due to restrictions on time and resources ( 46 ). Modifications to EBCD in this study align with best practice approaches for health co-design projects with Aboriginal and Torres Strait Islander people and communities ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, such an approach expands transformative research and cocreation in health marketing (Dahl, Peltier, and Milne 2018; Davey and Grönroos 2019; Frow, McColl-Kennedy, and Payne 2016; Mai and Wang 2019; Verleye et al 2017) by incorporating holism within health care (Gee and Walsemann 2009; McGuffog et al 2023). This is done by moving beyond considering the individual lived experiences of First Nations people as vulnerable consumers (Beatson et al 2020; Boenigk et al 2021) to assess the broader impacts of actants and networks.…”
Section: Discussionmentioning
confidence: 99%
“…We also believe our theoretical framework helps map the holistic perspective of First Nations people (Banerjee 2021; McPhail-Bell et al 2016; Wright et al 1997) and how this must be addressed in any positive health change (Gee et al 2014; McGuffog et al 2023) to overturn barriers of colonial structures in health services (Silberner 2021; Tsey and Every 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the previous reviews of Indigenous health research that have identified continued growth in outputs ( Kinchin et al, 2017 ), lack of intervention research and research in urban settings ( Jennings et al, 2021 ; McGuffog et al, 2023 ), and the need to hold to account health systems ( Kennedy et al, 2022 ), there have been limited attempts to explore the evolution and current state of knowledge structure of the research. In 2006, Sanson-Fisher et al (2006) examined the scientific literature related to the health of Indigenous peoples collectively from Australia, Canada, New Zealand and the United States at time points between 1987 and 2003.…”
Section: Introductionmentioning
confidence: 99%